Long-term exposure to fine particulate matter and development of chronic obstructive pulmonary disease in the elderly - Han, Changwoo; Oh, Jongmin; Lim, Youn Hee; Kim, Soontae; Hong, Yun Chul (Environment International, 2020)
Background: Studies evaluating the role of long-term exposure to fine particulate matter (PM2.5) on chronic obstructive pulmonary disease (COPD) development showed inconsistent results and were limited to Western countries. We aimed to determine the association between long-term exposure to PM2.5 and COPD development in metropolitan cities in Korea, which have higher PM2.5 levels than those in Western country studies. Methods: We constructed a retrospective cohort (elderly aged over 65 years who resided in 7 metropolitan cities in 2008) using Korea health insurance data. A total of 687,940 elderlies who had not visited hospitals due to COPD for 3 years (from 2008 to 2010) were followed-up from 2011 to 2016. The first hospital visit due to COPD during the follow-up period was regarded as COPD development. Daily district-level PM2.5 concentrations were estimated by chemical transport model and 60-month moving average PM2.5 were assigned to each subject in time-varying Cox proportional hazard model. Results: The mean concentration of modelled PM2.5 in 7 metropolitan cities during the study period (from 2006 to 2016) was 28.0 μg/m3 and 259,700 subjects newly visited the hospital due to COPD. COPD hospital visit hazard ratio for a 10 μg/m3 increase in 60-month moving average PM2.5 concentration was 1.09 (95% confidence interval: 1.07, 1.11). Risks remained unchanged following different PM2.5 exposure levels (48-month moving average, and average PM2.5 concentrations for 2008 and 2008–2010) and in subgroup analysis by subject characteristics (sex, age, and income groups). Discussion: By following-up 687,940 elderly subjects who resided in metropolitan cities in Korea for 6 years, long-term PM2.5 exposure showed association with COPD development.
Keywords: Chemical transport models; Chronic obstructive pulmonary disease; Confidence interval; Cox proportional hazard model; Fine particulate matter; Fine particulate matter (PM2.5); Mean concentrations; PM2.5 concentration; Aged; Air Pollutants; Air Pollution; Cities; Environmental Exposure; Humans; Particulate Matter; Pulmonary Disease, Chronic Obstructive; Republic of Korea; Retrospective Studies; Aged; Chronic obstructive pulmonary disease; Cohort studies; Particulate matter